The behaviour of axially loaded cold-formed steel back-to-back C-channel built-up columns - Ting, Chui Huon Tina (Curtin University, 2013)
Cold-formed steel built-up section is a preferred economical solution for buildings when a single section is insufficient. However, there are no comprehensive guidelines for the design of these sections. This project investigates the behaviour of axially-loaded cold-formed steel built-up columns through theoretical analysis, finite element modelling, and experimental studies. The results show that current design guidelines predict the built-up columns' capacity conservatively. An improved design method, TReM, is proposed.